EFEKTIFITAS BEBERAPA TANAMAN HIAS DALAM MENYERAP TIMBAL (Pb) DI UDARA - Baiq Mirawati; Muhlis -; Prapti Sedijani (Jurnal Penelitian Pendidikan IPA, 2016)
The objective of this reasearch was to determine the ornamental plants Lidah mertua (Sanseviera trifasciata.sp), Puring (Codiaeum variegatum), Palem Kuning (Chrysalidocarpus lutecsens) ability to absorb lead (Pb) concentration. This research is descriftive explorative research design with completely randomized design with 9 times treatments and 3 repetitions. The independent variables were lidah mertua (Sanseviera trifasciata.sp) Puring (Codiaeum variegatum), Palem Kuning (Chrysalidocarpus lutecsens), and the subjec variable is measurement of lead (Pb) concentration in the leaves. Data analysis techniques using qualitative and quantitative analysis. Quantitative data was obtained by calculating the lead (Pb) concentration in ornamental plants such as: Lidah mertua (Sanseviera trifasciata.sp) Puring (Codiaeum variegatum), Palem Kuning (Chrysalidocarpus lutecsens) by using AAS (Atomic Absorption Spectrophotometer) test.  Based on reasearch finding, there several finding of oranamental plants ability in absorb lead (Pb): lidah mertua (Sanseviera trifasciata.sp ): 0,06 ppm; 0,1 ppm; 0,15 ppm, puring (Codiaeum variegatum):  0,04 ppm; 0,09 ppm; 0,2 ppm and palem kuning (Chrysalidocarpus lutecsens): 0,02 ppm; 0,04 ppm; 0,11 ppm. Statistical test states that the type of plant and the traffic density does not affect the ability of plants to absorb lead (Pb).Keywords: Lead (Pb), lidah mertua (Sanseviera trifasciata.sp), Puring (Codiaeum variegatum), Palem Kuning (Chrysalidocarpus lutecsens).